2020
DOI: 10.1177/0748233719899824
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat stress on hematological parameters and oxidative stress among bakery workers

Abstract: Heat stress causes physiological changes, and changes in hematological parameters and hormonal levels in the human body, known as thermal strain. This study was conducted to determine the effect of exposure to heat stress on hematological parameters and oxidative stress in the bakers of Shahroud City, Iran. A total of 163 bakery workers (exposed group) and 135 office workers (unexposed group) with a minimum of 1-year working experience were selected. Exposure to heat stress was measured using ISO-7243 criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 40 publications
8
27
0
2
Order By: Relevance
“…Heat or thermal treatment is considered as one of the novel techniques for food preservation. For many years, the technique is well proven in various food sectors: from bakery and dairy to fruits and vegetables (Wurlitzer et al 2019 ; Gharibi et al 2020 ; Prieto-Santiago et al 2020 ; Christiansen et al 2020 ). The process generally involves heating of foods at a temperature between 75 and 90 °C or higher with a holding time of 25–30 s. Study on preservation enhancement of apple juice beverage by pasteurization and thermal treatment of maize showed a great impact on the flavor, digestibility, glycemic index, aroma, color and sensory attributes (Charles-Rodríguez et al 2007 ; Zou et al 2020 ).…”
Section: Prevalent Food Preservation Technologiesmentioning
confidence: 99%
“…Heat or thermal treatment is considered as one of the novel techniques for food preservation. For many years, the technique is well proven in various food sectors: from bakery and dairy to fruits and vegetables (Wurlitzer et al 2019 ; Gharibi et al 2020 ; Prieto-Santiago et al 2020 ; Christiansen et al 2020 ). The process generally involves heating of foods at a temperature between 75 and 90 °C or higher with a holding time of 25–30 s. Study on preservation enhancement of apple juice beverage by pasteurization and thermal treatment of maize showed a great impact on the flavor, digestibility, glycemic index, aroma, color and sensory attributes (Charles-Rodríguez et al 2007 ; Zou et al 2020 ).…”
Section: Prevalent Food Preservation Technologiesmentioning
confidence: 99%
“…18,19 While there is generally a dearth of literature on food service workers and heat stress, a few studies, such as those by Gharibi et al and Singh et al have identified heat as the source of adverse health effects, including inflammatory responses and changes in hematological parameters, among kitchen workers. 20,21 The majority of health and safety professionals rely on employee-level interventions such as light clothing, rest breaks, and hydration to control heat stress, and food service is no different. 14,22 Adequate ventilation can reduce heat exposure, but may lead to uneven temperatures throughout the establishment or present cooking difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…et al characterized baking goods as heavy labor under ACGIH Guidelines, this study chose to do the same, as the tasks are analogous in terms of effort 20. ACGIH recommended maximum temperature values stratified by work-rest regimens and type of work 25.…”
mentioning
confidence: 99%
“…Известно, что окислительный стресс играет важную роль в развитии различных патологических состояний, в том числе заболеваний сердечно-сосудистой системы и в частности -ИБС [9][10][11]. К сожалению, работы, посвященные исследованию свободнорадикальных процессов при тепловом стрессе in vivo и in vitro, крайне немногочисленны [12][13][14][15]. В экспериментальных исследованиях показано, что активные формы кислорода (АФК) стимулируют апоптоз в культивируемых эндотелиоцитах в процессе теплового стресса [12], а у мышей в условиях гипертермии увеличивается актив-ность антиоксидантного фермента супероксиддисмутазы (Cu,Zn-SOD) в печени [13].…”
unclassified
“…В экспериментальных исследованиях показано, что активные формы кислорода (АФК) стимулируют апоптоз в культивируемых эндотелиоцитах в процессе теплового стресса [12], а у мышей в условиях гипертермии увеличивается актив-ность антиоксидантного фермента супероксиддисмутазы (Cu,Zn-SOD) в печени [13]. У работников горячих цехов существенно увеличивался уровень вторичного продукта свободнорадикального окисления липидов -малонового диальдегида (МДА) в плазме крови [14], причем тепловой стресс увеличивал у испытуемых степень окисления глутатиона в крови [15]. При экспериментальной гипертермии у практически здоровых добровольцев нами отмечены изменения параметров, характеризующих наличие выраженного окислительного стресса [16,17].…”
unclassified